Research Advances in Cardio-Cerebrovascular Diseases of Ligusticum chuanxiong Hort. - Li, Dan; Long, Yu; Yu, Shuang; Shi, Ai; Wan, Jinyan; Wen, Jing; Li, Xiaoqiu; Liu, Songyu; Zhang, Yulu; Li, Nan; Zheng, Chuan; Yang, Ming; et al. (Frontiers in Pharmacology, 2022)
Cardio-cerebrovascular diseases (CVDs) is a serious threat to human health and accounts for 31 percent of global mortality. Ligusticum chuanxiong Hort. (CX) is derived from Umbellifer plants. Its rhizome, leaves, and fibrous roots are similar in composition, but in different contents. It has been used in Japanese, Korean and other traditional medicine for over 2000 years. Currently, it is mostly cultivation, and has high safety and low side effects. Due to the lack of a systematic summary of the efficacy of CX in the treatment of CVDs, this paper described the material basis, molecular mechanism and clinical efficacy of CX, as well as its combined application in the treatment of CVDs, and summarized from the perspective of safety. In particular, the pharmacological effect of CX in CVDs treatment was highlighted from the mechanism point of view and the complex mechanism network was determined. Improve understanding of CX’s multi-link and multi-target therapeutic effects, including antiinflammatory, antioxidant and endothelial cells. It offers a new perspective on the impact of CX on CVDs from a modern perspective.